Social impact assessment needed before projects, says Deputy VC - Chan, Neil (Daily Express, 2015)
KOTA KINABALU: Universiti Malaysia Sabah (UMS) Deputy Vice Chancellor (Research and Innovation) Prof. Dr Shahril Yusof on Friday stressed the need to conduct Social Impact Assessments before development projects are carried out.